Compliance with personal protective equipment use among non-medical healthcare professionals during Covid-19 pandemic - Estika Mei Diana; Anna Wahyuni Widayanti; Satibi (Universitas Gadjah Mada, 2021)
Non-medical healthcare professionals, including pharmacists, pharmacy technicians, nutritionists, and radiographers, have a high risk of  COVID-19 infection during work. Personal protective equipment use has shown effective in preventing virus transmission. This study aimed to investigate the compliance with personal protective equipment use and identify the factors that may influence their compliance. The study was designed cross-sectionally, with a self-administered questionnaire. The respondents were non-medical healthcare professionals recruited from covid and non-covid ward at Saiful Anwar General Hospital. The data were collected in November 2020. The questionnaire consists of four questions to assess compliance and eighteen questions to explore the factors that may relate to their compliance. This study used the Chi-square test to differentiate the level of compliance between two groups and binary logistic regression to analyze factors that may influence the compliance. Most participants in this study were female (84.8%), with a median age of 33 (23 - 57) years. More than 80 % of participants worked in the non-covid ward. Only one-fifth of participants had work experience of more than 15 years. The compliance with personal protective equipment was 67.3%. In univariate analysis, factors that influenced the compliance were difficulty using, removing, and disposing of personal protective equipment, lack of training and regular monitoring, unsure about the effectiveness of personal protective equipment, uncomfortable in donning personal protective equipment. Co-workers never reminding themselves to use personal protective equipment also influence compliance. In the multivariate analysis, the difficulty of using, removing and disposing of personal protective equipment (OR 2.83 (0.730 - 3.478), p=0.025) significantly influenced compliance with personal protective equipment use.